Retrospective Analysis of Semen Quality Using Sperm Enhancing Technique for Intrauterine Insemination (Bangladesh Journal of Urology, 2020)
Objective: To use sperm wash swim up technique as a diagnostic tool in Intra Uterine Insemination.Design: Male semen data was recorded for 181 couples who chose to undergo IUI procedures at the Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine & Metabolic Disorders (BIRDEM) Centre for Assisted Reproduction (CARE) from 2013- 2016. Couples were selected for IUI based on initial complaints of primary or secondary subfertility. The female partner had at least patent one tube based on hysterosalphingogram or laparoscopy results. Polycystic ovarian syndrome and minimal to mild endometriosis cases were included. Male factor includes sexual dysfunction and moderate sperm abnormalities.Statistical Analysis: Baseline and stratified analyses were conducted using semen data form.Results: There were 181 IUI cycles done in total. 126 couples (70%) suffered from primary sub fertility while 55 couples (30%) suffered from secondary subfertility. The baseline findings show that morphology of samples is improved by nearly 28%, while rapid linear motility improves by 50% after the first wash and has less variation after the second wash. Concentration, rapid linear motility, and morphology, all have strengthened parameters with each progressive wash process (p< .0001, p< .0001, and p = .0004, respectively).Conclusions: The result of our study provides some interesting observations in the treatment modalities for male infertility. Relatively low cost, less time consuming Swim up sperm wash technique can improve the quality of semen in a great extent.Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.36-41